2017
DOI: 10.1210/en.2017-00677
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Regulates Differentiation and Steroidogenesis in Female Mouse Ovarian Granulosa Cells

Abstract: The Notch pathway is a highly conserved juxtacrine signaling mechanism that is important for many cellular processes during development, including differentiation and proliferation. Although Notch is important during ovarian follicle formation and early development, its functions during the gonadotropin-dependent stages of follicle development are largely unexplored. We observed positive regulation of Notch activity and expression of Notch ligands and receptors following activation of the luteinizing hormone-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…The Notch pathway in GCs originates from gonadotropin signals and is important for oocyte development. Kinase cascade activation by the Jag1 ligand promotes GC differentiation and inhibits proliferation [ 34 ].…”
Section: The Main Metabolic and Signaling Pathways Involved In Phymentioning
confidence: 99%
“…The Notch pathway in GCs originates from gonadotropin signals and is important for oocyte development. Kinase cascade activation by the Jag1 ligand promotes GC differentiation and inhibits proliferation [ 34 ].…”
Section: The Main Metabolic and Signaling Pathways Involved In Phymentioning
confidence: 99%
“…In current investigation, we found that ligand-receptor pairs played important roles in goat folliculogenesis. Notch signaling pathway has been reported to be one of the most important pathways in folliculogenesis 38 . DLL3 , a ligand in Notch pathway, was highly expressed in oocytes, while another ligand in Notch pathways JAG2 was highly expressed in GCs compare with DLL3 and JAG1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to classifying as a key TF, HES4 is a DEx gene in our muscle samples. Signalling by genes of the Hes family is important to mediate cell-cell communication, differentiation and steroidogenesis in ovarian granulosa cells (Kageyama, Ohtsuka, & Kobayashi, 2007;Prasasya & Mayo, 2017). Overexpression of HES4 leads to increased expression of RUNX2, one of our hub genes, which is critical to osteoblast differentiation (McManus et al, 2017).…”
Section: Discussionmentioning
confidence: 99%